Natural mating of estrus-synchronized heifers and indicators of bull fertility - Pruitt, R.J.; Corah, L.R.; Simms, D.D.; Spire, M.F. (Kansas State University. Agricultural Experiment Station, 2011)
In six trials involving 486 heifers and 23 bulls, we studied factors affecting pregnancy rates of estrus-synchronized heifers mated naturally and evaluated indicators of bull fertility. Heavier heifers and those in fleshier condition had a higher response to estrus synchronization with Lutalyse. Heifers serviced more than once did not have higher pregnancy rates. Pregnancy rates achieved by bulls ejaculating up to 32 times in 2 1/2 days decreased only slightly as the number of ejaculations increased. There was considerable variation in pregnancy rates and the number of ejaculations achieved by individual bulls. Sex drive measured by a 3D-minute serving-capacity test was positively correlated with the number of ejaculations during the mating period and the number of heifers pregnant per bull. None of the variables studied could adequately explain the wide variation in pregnancy rates attributed to individual bulls.
Keywords: Beef; Heifers; Bull fertility; Lutalyse